Pedagogika społeczna i jej miejsce w systemie nauk pedagogicznych = Social pedagogy and its place in the system of pedagogical disciplines - Kawula, Stanisław (1939- ) (Zielona Góra: Uniwersytet Zielonogórski)
The dissertation presents a synthesis of different views on social pedagogy as an academic subdiscipline, which has become successful and has acquired high esteem both in Poland and abroad.
Keywords: pedagogika społeczna